Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top


How do you find the exact value of that?

I'm studying induction, and I'm still not sure how to get that value.

share|cite|improve this question
A related question. – J. M. Jul 5 '12 at 5:53

Let $$S=1+2+3+...+n$$ then, $$S=n+(n-1)+(n-2)+...+1$$ Adding corresponding terms of two equations gives , $$2S=(n+1)+(n+1)+(n+1)+...(n+1)=n(n+1)\implies S=n(n+1)/2$$ Now $$(n+1)^3-n^3=3n^2+3n+1$$ $$\implies 2^3-1^3=3(1)^2+3(1)+1$$ $$3^3-2^3=3(2)^2+3(2)+1$$ $$4^3-3^3=3(3)^2+3(3)+1$$ $$..$$$$..$$$$(n+1)^3-n^3=3(n)^2+3(n)+1$$ Adding corresponding terms gives, $$(n+1)^3-1^3=3(1^2+2^2+...+n^2)+3(1+2+...+n)+n$$ $$\implies n^3+3n^2+3n=3(ReqSum)+3n(n+1)/2+n$$ Solving for $ReqSum$ and factorization gives $ReqSum=n(n+1)(2n+1)/6$. For $n=100$, it is $100.101.201/6=338350$.

share|cite|improve this answer

The sum of squares formula is

$\sum_{i= 1}^n i^2 = \frac{n(n + 1)(2n + 1)}{6}$

Clearly it holds for $n = 1$.

Suppose it held for $n$. That is

$\sum_{i= 1}^n i^2 = \frac{n(n + 1)(2n + 1)}{6}$

Then $\sum_{i = 1}^{n + 1} i^2 = \sum_{i = 1}^n i^2 + (n + 1)^2 = \frac{n(n + 1)(2n + 1)}{6} + (n + 1)^2 = \frac{2n^3 + 2n + n}{6} + \frac{6(n^2 + 2n + 1)}{6}$

$=\frac{2n^3 + 9n^2 + 13n + 6}{6} = \frac{(n + 1)((n + 1) + 1)(2(n + 1) + 1)}{6}$

Thus by induction the formula holds.

Your series above is $\sum_{i = 1}^{100} i^2 = \frac{(100)(101)(201)}{6}$

share|cite|improve this answer

Some useful formulae, which are easy to prove by induction are:

$$\sum_{i= 1}^n 1 = n$$

$$\sum_{i= 1}^n i = \frac{n(n + 1)}{2}$$

$$\sum_{i= 1}^n \frac{i(i+1)}{2} = \frac{n(n + 1)(n+2)}{6}$$

$$\sum_{i= 1}^n \frac{i(i+1)(i+2)}{6} = \frac{n(n + 1)(n+2)(n+3)}{24}$$

In fact, there is a general form for this kind of expression which can be established by induction. This enables us to see that the sum of a quadratic expression will be a cubic one, the sum of a cubic expression will be quartic etc. It also gives a brute force way of summing any such formula - but there are often short cuts. I have found it useful to know the formulae for the sums of squares and cubes.

share|cite|improve this answer
+1: Might also want to point out that your formulas follow easily from Pascal's triangle :-). – Jyrki Lahtonen Jul 5 '12 at 6:22

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.